You are on page 1of 20



‫א‬
 ‫א‬

١

 ‫א‬W‫א‬‫א‬
 
 ‫א‬‫א‬‫א‬‫א‬W‫א‬‫א‬
 
 W‫א‬‫א‬
 W‫א‬‫א‬‫א‬
K‫א‬‫א‬ •

K‫א‬‫א‬ •

KE‫א‬‫א‬،‫א‬‫א‬‫א‬،‫א‬‫א‬F‫א‬‫א‬‫א‬ •

 K‫א‬‫א‬‫א‬‫א‬ •

 
 K٪٨٠‫א‬‫א‬W‫א‬‫א‬‫א‬
 
KW‫א‬‫א‬
 
 

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬     ‫א‬ ‫א‬K١   f : I → ℜ  I ≠ {x0 }، I  x0 ، ℜ I     b ‫א‬ x0  f ‫א‬‫א‬ f ( x) − f ( x0 )   f ′( x0 ) ‫ﺒ‬ x0  f  b  lim =b x → x0 . x ≠ x0 x − x0  I  x0        ‫א‬ I      f      ‫א‬‫א‬     f . lim ε (h) = 0    h→0   f ′( x0 ) ≠ ( f ( x0 ))′ W٢  ‫א‬‫א‬‫א‬K٢  f ‫ ﻠ‬‫א‬ C f ‫א‬ x0  f  ( x0 . : I → ℜ       x → f . ( x)      f ‫א‬‫א‬  ε  b ‫א‬‫א‬ x0  f W١    ( x0 + h)  f ( x0 + h) = f ( x0 ) + bh + hε (h) . f ( x0 )) ‫א‬‫א‬‫א‬ M 0 ‫א‬   f ( x) − f ( x 0 ) NM   (D) ‫א‬ = =   x − x0 M0N         M 0  C f ‫ ﻠ‬‫א‬ M 0T  (D) ‫א‬ x0  x  .

.... f n ( x)  F ( x) = f1 ( x) ± f 2 ( x) ± .. ‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬     ‫א‬‫א‬‫א‬K٣ n ‫א‬‫א‬‫א‬‫א‬‫א‬ W١‫א‬   y = f ( x) = x n W‫א‬‫א‬   y′ = nx n−1      y = x 3 ‫א‬W٧   y′ = 3x 3−1 = 3x 2      y = x − 4 ‫א‬W٨   y′ = −4 x −4 −1 = −4 x −5     1 ‫א‬ y = x    y = x ⇒ y ′ = 1x1−1 = x 0 = 1     y′ = 0  c  y = c ‫א‬‫א‬‫א‬:٢‫א‬   y′ = 0  y = −5 ‫א‬ y′ = 0  y = 7 ‫א‬W٩   y′ = nax n−1  y = ax n ‫א‬‫א‬W٣‫א‬   y = 3x 6 ‫א‬W١٠   y′ = 3 × 6 x 6−1 = 18 x 5     y = 53 x ‫א‬‫א‬W١١  W‫א‬ 1  y=5 x = 3 5( x) 3    1 −2 1 −1 5   y′ = × 5 x 3 = x 3   ‫א‬ 3 3  ‫א‬‫א‬W٤‫א‬  f1 ... ± f n−1 ( x) ± f n ( xn )  ‫א‬   y = 4 x −3 − 5 x 2 + 7 x − 12 ‫א‬‫א‬W١٢   y′ = −3 × 4 x −3−1 − 5 × 2 x 2−1 + 7 x1−1 = −12 x −4 − 10 x + 7      . ± f n −1 ( x) ± f n ( x) ‫א‬ F (x) ‫א‬‫א‬   F ′( x) = f1′( x) ± f 2′( x) ± ..

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬     ‫א‬‫א‬W٥‫א‬ ‫א‬ f1 ( x). f 2 ( x)   F ( x) = f1 ( x). f 2 ( x)  ‫א‬   F (x)  ‫א‬‫א‬     F ′( x) = f1′( x) f 2 ( x) + f 2′ ( x) f1 ( x)  K ℜ  I ‫א‬   F ( x) = (3x − 2)(4 x + 1) ‫א‬‫א‬W١٣ F ′( x) = 3(4 x + 1) + 4(3 x − 2)    = 12 x + 3 + 12 x − 8 = 24 x − 5     ‫א‬W٦‫א‬ f1 ( x )  f1 ( x). f 2 ( x)  F ( x) = ‫א‬ F (x) ‫א‬‫א‬  f 2 ( x)  K ℜ  I ‫א‬ f 2 ( x) ≠ 0  ℜ  I ‫א‬ f1′( x) f 2 ( x) − f 2′ ( x) f1 ( x)   F ′( x) = ( f 2 ( x) )2 1 8x7   x ≠  y = ‫א‬‫א‬W١٤ 2 2x − 1  W‫א‬   f 2 ( x) = 2 x − 1 ⇒ f 2′( x) = 2  f1 ( x) = 8 x 7 ⇒ f1′( x) = 7 × 8 x 7−1 = 56 x 6     ‫א‬ f1′( x) f 2 ( x) − f 2′ ( x) f1 ( x) 56 x 6 (2 x − 1) − 2 × 8 x 7 56 x 6 (2 x − 1) − 16 x 7 F ′( x) = = = ( f 2 ( x)) 2 (2 x − 1) 2 (2 x − 1) 2    7 6 112 x − 56 x − 16 x 7 96 x − 56 x 7 8 x (12 x − 7 ) 6 6 = 2 = 2 = (2 x − 1) (2 x − 1) (2 x − 1) 2           F ( x) = ( f ( x)) n ‫א‬‫א‬‫א‬‫א‬W٧‫א‬   f (x)  F ( x) = ( f ( x)) n ‫א‬    F ′( x) = n( f ( x)) n −1 f ′( x)   y = F ( x) = 4(2 x 2 + 3x − 2) 2 ‫א‬‫א‬W١٥  W‫א‬   f ( x) = (2 x 2 + 3x − 2) ⇒ f ′( x) = 4 x + 3      y′ = F ′( x) = 2 × 4(2 x 2 + 3x − 2) 2−1 (4 x + 3) = 8(2 x 2 + 3x − 2)(4 x + 3) ‫א‬ .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬        W‫א‬‫א‬ 1) y = (2 x 3 − 7)(3x 2 ) 6) y = (3x − 2)( x + 7) ⎛ 2x − 7 ⎞ −1 4 3x − 1 11) y = ⎜⎜ ⎟ (3 − 2 x) 3 2 ⎟ 16) y = ⎝ x ⎠ x2 −2 2x2 − 5 3x 2 3 x −1 ⎞ 2 2) y = 7) y = 12) y = ⎛⎜ 3 2 3x (5 x + 7)(2 x − 1) ⎟ 17) y = x (5 x + 1) 3 ⎝ x + 2⎠ 3) y = 2 8) y = (2 x 4 − 1.8 5 x3 + 4 2 14) y = x x − 1 19) y = (4 x 2 x 3 ) 1 4) y = 3 9) y = 2 4 4 x − 3x 2 x ( x − 2) 3 5) y = 1 −x 10) y = (2 x 3 − 4 x + 7) −2 15) y = 1.9) 3 13) y = 2 2x 18) y = 2 x −3 + 7 x −5 3x 2 − 7 x + 4 x + 1.9 20) y = x−2 x+2 ( 2 x + 4) 3 x2 + 5 .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬     W‫א‬‫א‬‫א‬‫א‬K٤  ℜ I‫א‬ x ‫א‬ u  y = sin u ‫א‬‫א‬ E١   y′ = dy = d (sin u ) du = cos u du     dx du dx dx    ℜ I‫א‬ x ‫א‬ u  y = cos u ‫א‬‫א‬E٢   y ′ = dy = d (cos u ) du = − sin u du     dx du dx dx   y = sin(2 x 3 − 3) ‫א‬‫א‬W١٦   y′ = 3 × 2 x 2 cos(2 x 3 − 3) = 6 x 2 cos(2 x 3 − 3)    y = cos(2θ 3 − 3θ −2 ) ‫א‬‫א‬W١٧  W‫א‬ du   u = 2θ 3 − 3θ −2 ⇒ = 6θ 2 + 6θ −3    dθ   y′ = −(6θ + 6θ ) sin(2θ 3 − 3θ −2 )  2 −3  ‫א‬     ℜ I‫א‬ x ‫א‬ u  y = tan u ‫א‬‫א‬E٣   y′ = dy = dy du = d (tan u ) du = sec 2 u du     dx du dx du dx dx dy    y = tan x −2 ‫א‬W١٨ dx  W‫א‬ du   u = x−2 ⇒ = −2 x − 3   dx   y ′ = d (tan u ) = du sec 2 u = −2 x −3 sec 2 x −2  ‫א‬ dx dx     ℜ I‫א‬ x ‫א‬ u  y = cot u ‫א‬‫א‬E٤   y ′ = dy = dy du = d (cot u ) du = − csc 2 u du dx du dx du dx dx     .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬      y = cot 3x ‫א‬‫א‬‫א‬W١٩  W‫א‬ du   u = 3x ⇒ = 3    dx   y ′ = d (cot u ) = − du csc 2 u = −3 csc 2 3 x   dx dx   ℜ I‫א‬ x ‫א‬ u  y = sec u ‫א‬‫א‬E٥ dy dy du d (sec u ) du du   y′ = = = = tan u sec u dx du dx du dx dx   y = secθ 2 ‫א‬‫א‬‫א‬W٢٠  W‫א‬ du  u = θ 2 ⇒ = 2θ   dθ   y ′ = d (sec u ) = du tan u sec u = 2θ tan θ 2 secθ 2    dθ dθ     ℜ I‫א‬ x ‫א‬ u  y = csc u ‫א‬‫א‬E٦   y ′ = dy = dy du = d (csc u ) du = − du cot u csc u dx du dx du dx dx   y = csc x 3 ‫א‬‫א‬‫א‬W٢١  W‫א‬ du   u = x3 ⇒ = 3x 2    dx   y ′ = d (csc u ) = − du cot u csc u = −3 x 2 cot x 3 csc x 3    dx dx   y = csc(2 x 5 − 3) ‫א‬‫א‬‫א‬W٢٢  W‫א‬ du   u = 2x5 − 3 ⇒ = 10 x 4    dx   y ′ = d (csc u ) = − du cot u csc u = −10 x 4 cot( 2 x 5 − 3) csc(2 x 5 − 3) dx dx     .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬    W‫א‬‫א‬‫א‬‫א‬‫א‬W 1) y = sin 5 3 x 2 5) y = csc 3 (−7 x 4 ) sin x 2 13) y = sin (cos 2 x ) 9) y = cos 2 x 2 1 6) y = 1 + cos 2 x 5 14) y = 1 + sin x 2) y = x tan 10) y = sec(2 x + 1)2 x 3) y = x cos 2 x 7) y = tan 2 ( x 2 + 1) 1 15) y = x cot (− 4 x ) 11) y = x 2 sin 3 x 12) y = (sin x − cos x ) 16) y = x csc x 2 4) y = csc x 3 8) y = ( x 4 − cot x) 3 .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬     ‫א‬ ‫א‬‫א‬‫א‬‫א‬K٥  ‫א‬‫א‬‫א‬‫א‬‫א‬K١{٥   x ‫א‬ u  y = ba u ‫א‬‫א‬‫א‬W١‫א‬ dy   = ba u ln a u ′        dt   y = 8 2 (3 x )W‫א‬‫א‬‫א‬‫א‬W٢٢ 2 + 4 x +5  W‫א‬ ln 2 (6 x + 4 ) = (48 x + 32) ln 2 23 x 2 2   y′ = 8 23 x + 4x +5 +4x+5       e ≅ 2. W‫א‬‫א‬‫א‬‫א‬  5 6x x x . a ≠ 1  y = b log a u ‫א‬‫א‬‫א‬W١‫א‬  W‫א‬‫א‬ dy dy du u′   = = b log a e       dx du dx u   y = 3 log(6 x 5 ) W‫א‬‫א‬‫א‬‫א‬‫א‬W٢٥  W‫א‬   y′ = ( ) 3 30 x 4 log e 15 x 4 15 = 5 log e = log e.718 ‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬W٢‫א‬   x ‫א‬ u  y = b eu ‫א‬‫א‬‫א‬ dy   y′ = = b e u u ′        dt   y = 8 e 2 x+1 W‫א‬‫א‬‫א‬‫א‬‫א‬W٢٣  W‫א‬ y′ = 8 × 2 e 2 x +1 = 16e 2 x +1 W‫א‬‫א‬‫א‬‫א‬    y = −5 e sin x ‫א‬W٢٤   y′ = −5 cos x e sin x      ‫א‬‫א‬‫א‬‫א‬‫א‬K٢{٥   x ‫א‬ u  a > 0.

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬      x ‫א‬ u  y = ln u  ‫א‬‫א‬‫א‬W٢‫א‬ dy u ′   y′ = =        dx u   y = e − x ln x 2 W‫א‬‫א‬‫א‬‫א‬W٢٦  W‫א‬ 2x −x ⎛ 2 ⎞   y ′ = −e − x ln x 2 + 2 e = ⎜ − ln x 2 ⎟e − x    x ⎝x ⎠  W‫א‬‫א‬‫א‬‫א‬‫א‬W ( 1) y = log 3 3 x 2 − 5 ) 5) y = ln x4 9) y = e x 2 13) y = e − x ln x (3 x − 4) 2 2) y = ln( x + 3) 6) f ( x) = ln sin 3x 14) y = e −2 x sin 3x 2 2 10) y = 53 x 3) y = ln 2 ( x + 3) ( 7) f ( x) = ln x + 1 + x 2 ) 11) y = x 2 3 x 15) f ( x) = ln tan e x 2 ( )( 4) y = ln x 2 + 2 x 2 + 3 ) 8) y = e 1 − x 2 12) y = 5e sin 2 x − x 16) f ( x) = ln 1 − 2 x   .

y   dx dy y   =− dx x  W‫א‬‫א‬(2) dy 1   =− 2 dx x ‫א‬‫א‬‫א‬‫א‬‫• א‬   f ( x. ‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬     ‫א‬‫א‬K٦  y ‫א‬‫א‬ x ‫א‬ f ( x. y ) = 0 W‫א‬ . y ) = 0 ‫א‬‫א‬‫א‬‫א‬   W٢٧   xy = 1 (1) dy  W‫א‬(1) ‫א‬ ‫א‬‫א‬‫א‬ dx 1  y= (2) x  W‫א‬ dy d ⎡ 1 ⎤ 1   = ⎢ ⎥=− 2 dx dx ⎣ x ⎦ x  x ‫א‬‫א‬ y (1) ‫א‬  W،E‫א‬‫א‬F‫א‬، d d d d dy   ( xy ) = (1) ⇒ x ( y ) + y ( x) = 0 ⇒ x + y = 0  dx dx dx dx dx dy   x.

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬      x. y ) = 0 dy  W W٢٨ dx   xy 3 − 3x 2 = xy + 5 (1)      W‫א‬  W (1) ‫א‬  y 3 + 3 xy 2 y ′ − 6 x = y + xy ′ ⇒ 3 xy 2 y ′ − xy ′ = y − y 3 + 6 x   ⇒ y ′[x(3 y 2 − 1)] = y − y 3 + 6 x       y − y3 + 6x ⇒ y′ = x(3 y 2 − 1)   y ′ ‫א‬‫א‬ x 2 − 2 xy + y 2 = 0 W٢٩  W‫א‬  W‫א‬‫א‬ d 2 d ( x − 2 xy + y 2 ) = (0) dx dx   ⇒ 2 x − 2 y − 2 xy ′ + 2 yy ′ = 0     2 y − 2x ⇒ y ′(2 y − 2 x) = 2 y − 2 x ⇒ y ′ = =1 2 y − 2x   . y  y′ ‫א‬‫א‬‫א‬  x ‫א‬ y ‫א‬‫א‬ •   x. y ) = 0 ‫א‬ d(yn ) dy   = ny n−1 = ny n−1 y ′ dx dx ‫א‬ x ‫א‬ y  x ‫ﻟ‬ y ‫א‬   f ( x. y  y′ ‫א‬    W x ‫ﻟ‬ y n ‫א‬ y ‫א‬‫א‬ x ‫א‬ f ( x.

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬     W‫א‬‫א‬‫א‬‫א‬‫א‬W٣٠ 2 2 1 1 x+ y  1) 5 y + sin y = x . y  y ′ ‫א‬‫א‬ 2x   y′ = 10 y + cos y   W‫א‬‫א‬‫א‬ d ⎡1 1⎤ d 2) ⎢ + ⎥ = (1) ⇒ − y −2 y ′ − x −2 = 0 dx ⎣ y x ⎦ dx  x −2 y 2 ⇒ y′ = − = y − 2 x2 3) d ⎡ 2⎤ d ⎡x + y⎤ x = ⎢ ⇒ 2 = (1 + y′)(x − y ) − (1 − y′)(x + y ) dx ⎢⎣ ⎥⎦ dx ⎣ x − y ⎥⎦ x (x − y )2 ⇒ 2 x( x − y ) = (1 + y ′)( x − y ) − (1 − y ′)( x + y ) 2  ⇒ 2 x( x − y ) = y ′( x − y + x + y ) + x − y − x − y 2 ⇒ 2 x( x − y ) = y ′(2 x ) − 2 y 2 2 x( x − y ) + 2 y 2 y ⇒ y′ = (x − y ) + 2 ⇒ y′ = 2x x           . 2) + = 1. 3) x 2 = 2 2 4) x 3 − y 3 − y = 1 y x x− y  ‫א‬   x ‫ﻠ‬‫א‬ (1   d dx [ 5 y 2 + sin y = dx ] d 2 [ ] x ⇒ 10 yy ′ + y ′ cos y = 2 x   (10 y + cos y ) y′ = 2 x    x.

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬    2 2 ( 4) x − y 3 − y = 1 3 1 1 2 −3 2 −3   ⇒ x − y y′ − y′ = 0 3 3 ⎛ −1 ⎞ 1 −1 ⎜2 ⎟ 2 − 2 x 3 ⇒ y ′⎜ y 3 + 1⎟ = x 3 ⇒ y ′ = ⎜3 ⎟ 3 3 ⎛ −1 ⎞ ⎝ ⎠ ⎜2 3 ⎟ ⎜⎜ 3 y + 1⎟ ⎟ ⎝ ⎠ ‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬  KW‫א‬‫א‬‫א‬   y = x x ‫א‬ y′ W٣١    W‫א‬   y = x x ⇒ ln y = ln x x ⇒ ln y = x ln x    W‫א‬ y′ ⎛1⎞   = ln x + x⎜ ⎟       y ⎝ x⎠ y′   = ln x + 1 ⇒ y ′ = y (ln x + 1) y   y = x x (ln x + 1)  y = x x     ‫א‬‫א‬‫א‬‫א‬‫ א‬W١ 1) xy + e xy − y 3 sin x = y 3 + 9 x cot y 7) x 2 = 1 + csc y 2) 3x 2 y 2 + 4 xy − 2 y = 0 8) tan 3 ( xy 2 + y ) = x 3) x 3 y 2 − 5 x 2 y + x = 1 3 9)3x 2 − 4 y 2 = 7 1 1 4) + = 1 10) y 3 sin x − x 2 = y 3e 2 x y x 5)( x 2 + 3 y 2 ) 3 = x 11) y + sin y = x .

−1) 3) y 2 − x + 1 = 0.1) 2) x 3 − y 3 − y = 1.‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬    2 2 12) x cos y = y 6) xy 3 + yx 3 = x2 W‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬W٢ 2 2 1) x 2 y − 5 xy 2 + 6 = 0.3) 1− y 4) = x. (0. (10. (1. (3.1) 1+ y .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬    ‫א‬‫א‬‫א‬K٧  W  f (x) ‫א‬ (n − 1) ‫א‬‫א‬ f (x) ‫א‬ n ‫א‬‫א‬  ‫א‬‫א‬ n ‫א‬‫א‬ ‫א‬ n ‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬  n ‫א‬‫א‬ n − 1 ‫א‬‫א‬KKKK‫א‬‫א‬‫א‬‫א‬  K ℜ ⊃ I ‫א‬‫א‬‫א‬ n  f  x ‫א‬ y  y = f (x)   W‫א‬‫א‬ dy d ( f ( x) )  E x ‫ﻟ‬ y ‫ﻟ‬‫א‬‫א‬F y ′ = = = f ′( x) dx dx d 2 y d ( f ′( x) )  E x ‫ﻟ‬ y ‫ ﻟ‬‫א‬‫א‬F y ′′ = = = f ′′( x) dx 2 dx d 3 y d ( f ′′( x) )  E x ‫ﻟ‬ y ‫ﻟ‬‫א‬‫א‬F y ′′′ = 3 = = f ′′′( x) dx dx d 4 y d ( f ′′′( x) )  E x ‫ ﻟ‬ y ‫ ﻟ‬‫א‬‫א‬F y ( 4) = 4 = = f ( 4) ( x) dx dx  KKKKKKKK  KKKKKKKK  KKKKKKKK  E x ‫ﻟ‬ y ‫ﻟ‬ n F y ( n) = n = ( d n y d f ( n−1) ( x) ) = f ( n) ( x) dx dx   y = sin x ‫א‬‫א‬‫א‬ W٣٢ d sin x y′ = = cos x     W‫א‬ dx d cos x   y ′′ = = − sin x dx d3y   y = 6x ‫א‬E‫א‬‫א‬F 5 W٣٣ dx d dx ( )   y ′ = 6 x 5 = 5 × 6 x 4 = 30 x 4    W‫א‬ d dx ( )   y ′′ = 30 x 4 = 4 × 30 x 3 = 120 x 3      .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬      y ′′′ = d dx ( ) 120 x 3 = 3 × 120 x 2 = 360 x 2      K‫א‬ n + 1 ‫א‬‫א‬ n ‫א‬ y ‫א‬W   y = 2 x 5 + 3x 3 + 5 x − 1 ‫א‬ y (6) W٣٤  W‫א‬   y (6) = 0 ‫א‬‫א‬ y             y′′  y = e − x ln x ‫א‬W٣٥    W‫א‬ −x −x d y′ = e − x dx dx ( ) (ln x ) + ln x d e − x = e − e − x ln x = e − y x x     − xe − x − e − x − xe − x − e − x e − x ⎛ 2 1 ⎞ y ′′ = 2 − y′ = 2 − + e − x ln x = −e − x ⎜ + 2 − ln x ⎟ x x x ⎝x x ⎠   y′′  y = e − x ln x 2 ‫א‬W٣٦   y = e − x ln x 2 = 2e − x ln x W‫א‬   y ′′ = −2 e − x ⎛⎜ + ⎞ 2 1 2 − ln x ⎟  ‫א‬‫א‬ ⎝x x ⎠   y′′  y = e −2 x sin 3x ‫א‬W٣٧  W‫א‬ −2 x   y ′ =e d dx dx ( ) (sin 3x ) + sin 3x d e −2 x = 3e −2 x cos 3x − 2e −2 x sin 3x = 3e −2 x cos 3x − 2 y −2 x y ′′ = 3 e d dx dx ( ) (cos 3x ) + 3 cos 3x d e −2 x − 2 y ′ (   = −9e −2 x sin 3x − 6e −2 x cos 3x − 2 3e −2 x cos 3x − 2e −2 x sin 3x ) = − e −2 x (12 cos 3 x + 5 sin 3 x )    (t ) ‫א‬ feet (s ) ‫א‬ W   s = t 3 − 2t    ‫א‬٤ t ‫א‬‫א‬‫א‬ E١ .

‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬    ‫א‬٤ t ‫א‬‫א‬‫א‬ E٢   2 fet sec 2 ‫א‬‫א‬‫א‬ E٣  ‫א‬  ‫א‬‫א‬‫א‬E١ ds  ‫א‬‫א‬ (t ) ‫א‬ (t ) ‫א‬‫א‬ = 3 t 2 − 2  dt ds(4 )   dt ( = 3t 2 − 2 ) (4 ) − 2 = 46 ft sec ‫א‬4‫א‬ t =4 = 3 2  ‫א‬E‫א‬F‫א‬E٢ d 2s  ‫א‬‫א‬ (t ) ‫א‬ (t ) ‫א‬‫א‬ 2 = 6 t  dt  ‫א‬4‫א‬ d 2s 2 t =4 = 6 t t =4 = 6 × 4 = 24 ft sec 2    dt   2 fet sec 2 ‫א‬‫א‬‫א‬(٣ d 2s 1   = 6 t = 2 ⇒ t = sec dt 2 3   .

8t 3 − 2. y ′′ 5 3 d6y 7) y = 3 x − 10 x + 15 x . 6 dx 1 1 x d y2 2) y = x 3 − x 5 . x − 2 4 dx 3 5) y = x( x − 1) 3 .9t 2 − 1 . y ′′ x +1 4) y = 8 x 3 − 2 x 4 . y ′′ 1 11) y = . x = 1 3) f ( x) = . y ′′  W‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬‫א‬:٢ 10 8 5 4x2 1) f ( x) = 8 x + 2 x − 4 x + 1 . t = 2h 3) s = t 2 1 + t 2 . t = 4h 2t 2 − 3 2) s = 3. x = −1  ‫א‬‫א‬‫א‬‫א‬ t (h) ‫א‬ s (km) ‫א‬W٣ t 1) s = (2t 2 − 3) 4 . t = 3h .4 − t 4 . y ′′′ 2x 9) y = 2 . x=2 3x − 7 2) f ( x) = 4 − x + 2 x 4 . y ′′ 8) y = . y′′ 12) y = (1 + x 2 ) ln x . t = 1h 6) s = 1. x = 1 4 ) f ( x ) = 2 x 2 2 x 4 + 3 . ‫א‬‫א‬ ١١٦  ‫א‬ ‫א‬    W  W‫א‬‫א‬‫א‬‫א‬W١ 1) y = 3x 2 − 2 x 3 . y ′′ x2 − 1  6) y = e −2 x (cos 3x − sin 2 x) . t = 2 h 4) s = . y ′′′ 1 x d3y 10) y = + . 2 3 5 x − 4 dx 3) y = 7 + 6 x 2 − 4 x 4 . t = 1h 5) s = (2t + 7) t 3 − 1 .